Analisis Pengaruh Pendidikan Vokasi SMK, Jumlah Tenaga Pendidik Dan Jumlah Satuan Pendidikan Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Timur Tahun 2019-2023 - Herlangga Prasetya Putra Pariswari Santoso; Renta Yustie (Widya Balina, 2025)
This study aims to analyze the influence of vocational education in vocational high schools, the number of educators, and the number of educational units on economic growth, particularly in vocational education in vocational high schools in districts or cities in East Java that have participated in education in both the formal and informal sectors in 38 districts or cities in East Java from 2019 to 2023. The research method used is a quantitative approach with data collection through secondary written sources or existing documents from relevant agencies, such as the Directorate General of Early Childhood Education, Basic and Secondary Education, the Central Statistics Agency of East Java Province, and the Ministry of Basic and Secondary Education. The dependent and independent variables were collected from thirty-eight districts and cities in East Java Province during the period 2019–2023. The analysis results indicate that Vocational Education has a significant impact on Economic Growth, with a significance value of 0.000 and a calculated t-value of 1.463392. Additionally, the Number of Educators shows a significant influence on Economic Growth, with a significance value of 0.000 and a calculated t-value of 7.710562. Furthermore, the number of educational institutions has a significant influence on economic growth, with a significance value of 0.000 and a t-value of 6.596880. The coefficient of determination (R²) indicates that 71.28% of the variation in economic growth can be explained by these three independent variables. This study concludes that both Vocational Education at SMK, the Number of Educators, and the Number of Educational Units play a significant role in influencing Economic Growth across all Vocational Education at SMK in the districts or cities of East Java.